Tax penalties and their effectiveness in reducing the creative accounting practices: An Empirical Study of the General Commission for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to study and definition of the concept of creative accounting and motives adopted by the management of companies to achieve their own goals and their impact on the reliability of the financial statements and the tax settling accounts and whether that tax administration is able to detect and limit the creative accounting practices and impose legal sanctions deterrent against companies The research has come to a set of conclusions, including:• The administration motives in the use of creative accounting methods, some internal motives related to the interests of the administration in maximizing profits to increase incentives and rewards, others are external, such as the impact on stock prices or reduce the amount of tax calculated on the company for the purpose of tax evasion.• The use of punishments stipulated by the Income Tax Act No. 113 of 1982 amended  As stated in the articles (58-59) helps companies reduce the practice of creative accounting methods and repeated in the future.Recommended Find the need to develop a tax examination system to include we cause enough of the taxpayers and the discovery of irregularities and accountability in order to pay the holders of the permit complete information and the right for access they earn and the need to activate the prison sentence prescribed in the Income Tax Act under the penalties in charge of the right, which has proved the resurrection of the practices of fraud and fraud, as the impact is greater than the impact of financial penalties to be imposed on the taxpayer, as well as to curb such practices in the future.